The role of glutamate in rotator cuff tendinopathy - Dean, B (2015)
Thesis questions: Is the glutaminergic system altered in rotator cuff tendinopathy? Is the glutaminergic system altered by common treatments? Are glutaminergic changes related to pain symptoms? What are the effects of glutamate and glutamate receptor modulation on tendon derived cells? Summary answers: The glutaminergic system is altered in rotator cuff tendinopathy Changes within this system are seen after common treatments Specific glutaminergic changes are associated with the resolution of pain following shoulder surgery but do not predict the severity of pain symptoms Glutamate has significant effects on tendon derived cells What is known: It is known that extracellular glutamate concentrations are increased in both Achilles and patellar tendinopathy. It has also been previously shown that the glutamate receptors NMDAR1 and mGluR5 are upregulated in patellar tendinopathy. What this thesis adds: This thesis has shown for the first time that glutamate and NMDAR1 are increased in rotator cuff tendinopathy. Increases in cell proliferation, vascularity and HIF1α are seen after surgical rotator cuff repair and these features are not seen after glucocorticoid injection. There are significant differences between painful and pain-free rotator cuff tendons in terms of glutamate receptor expression (KA1, mGluR7 and mGluR2) and inflammatory cell numbers (CD45 and CD206). Exposure to 1.875mM glutamate for 72 hours results in reduced cell viability, decreased collagen (COL1A1 and COL3A1) and increased aggrecan gene expression; NMDAR antagonism with MK-801 attenuates the deleterious effect on cell viability but had no effect on the changes in matrix gene expression. Bias, confounding and other reasons for caution: The observational histological work was limited by the control tissue. Some control tissue was not age matched, while some of the pain-free control tendons were post-surgical intervention. Confounding factors include tendon structure, length of symptoms and previous treatments. Caution must be applied when discussing the in vivo implications of the in vitro work. Study funding/potential competing interests: This thesis was funded by the Jean Shanks Foundation and Orthopaedic Research UK.